2011
DOI: 10.2340/16501977-0645
|View full text |Cite
|
Sign up to set email alerts
|

Facial paresis after stroke and its impact on patients’ facial movement and mental status

Abstract: Orofacial therapy has a significant effect after 4 weeks of treatment on facial movement and mental state in patients with stroke. Based on the results in our study we can say that the improvements are a significantly better in the experimental group (Difference value) in the parameters HBGS, distance between the corner of the mouth and earlobe and BDI-II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 5 publications
0
30
0
2
Order By: Relevance
“…OFR has impact not only on the restoration of the swallowing but also on the other orofacial functions (mimics, speech), overall health and life quality 4,8 . A newly recommended approach for the functional restoration of swallowing muscles is electrical stimulation (ES) of hyoid muscles.…”
Section: Introductionmentioning
confidence: 99%
“…OFR has impact not only on the restoration of the swallowing but also on the other orofacial functions (mimics, speech), overall health and life quality 4,8 . A newly recommended approach for the functional restoration of swallowing muscles is electrical stimulation (ES) of hyoid muscles.…”
Section: Introductionmentioning
confidence: 99%
“…This higher order regulation may indicate that activity on demand is dependent on correct information from both cortical sides and may explain our findings of bilateral dysfunction in the lower as well as in the upper facial quadrants. Dysfunction in all facial quadrants will likely also have emotional implications owing to the face's inability to express feelings [12]. …”
Section: Discussionmentioning
confidence: 99%
“…In their study, Volk et al (6) reported that a high percentage of patients continued to present with CFP 3 weeks post-onset, and over 60% of these patients were discharged from sub-acute rehabilitation with deficits persisting for more than 41 days post-stroke. As the available literature suggests that CFP can persist past the initial acute phase of stroke and not resolve spontaneously, people with CFP may benefit from access to a specific rehabilitation program aimed at maximizing recovery of facial movement and function (6,13,16).…”
Section: Introductionmentioning
confidence: 99%